Anti-inflammatory cytokines in autism spectrum disorders: A systematic review and meta-analysis - Saghazadeh, Amene; Ataeinia, Bahar; Keynejad, Kimia; Abdolalizadeh, Amirhussein; Hirbod-Mobarakeh, Armin; Rezaei, Nima (Cytokine (Philadelphia, Pa.), 2019)
•In the search for the causes of autism, inflammatory markers have emerged as potential candidates.•Studies have provided inconsistent results on altered levels of cytokine in patients with autism.•Meta-analyses show lower levels of IL-10 and IL-1Ra in autistic patients compared with controls.•Meta-analysis shows slightly higher levels of serum IL-5 in patients with autism.•Meta-regression shows that latitude, age, and gender influence alteration of IL-5, -10, and -1Ra in autism. In the search for the causes of autism spectrum disorders (ASD), inflammatory markers have emerged as potential candidates. The present meta-analysis was performed on studies examining circulating concentrations of anti-inflammatory cytokines in people with ASD compared with control subjects without ASD. We identified potentially eligible studies by systematically searching electronic databases from inception to February 2018. Twenty-five studies with a total of 1754 participants (1022 patients with ASD and 732 control subjects) were included in the mate-analysis; 4 for interferon (IFN)-α, 9 for interleukin (IL)-1 receptor antagonist (Ra), 9 for IL-4, 6 for IL-5, 3 for IL-9, 14 for IL-10, 7 for IL-13, and 6 for transforming growth factor (TGF)-β. We found a moderate decrease in plasma levels of IL-10 (SMD = −0.59) and a small decrease in serum levels of IL-1Ra (SMD = −0.25) in patients with ASD. On the contrary, serum IL-5 levels were slightly increased (SMD = 0.26) in these patients. We conducted meta-regression analyses to investigate the possible effect of moderatos on the effect size (ES) of difference in mean levels of IL-10. Difference in the mean age between patients and controls showed a negative influence on the ES and was able to explain about 0.4 of total between-study variance. In contrast, latitude exerted a positive effect on the ES and explained a lower proportion (0.1) of total between-study variance. This meta-analysis provides evidence for the lower concentration of anti-inflammatory cytokines IL-10 and IL-1Ra in autistic patients compared with control subjects. Also, meta-regression analyses point to the interaction of latitude, age, and gender with peripheral alterations of associated anti-inflammatory cytokines.